MANAGEMENT OF ACUTE TRISMUS IN PATIENTS WITH HEAD AND NECK CANCERS - Ben Birkenfeld; Michael D. Stubblefield (Journal of Cancer Rehabilitation, 2023)
Background Trismus, a common complication in head and neck cancer survivors, negatively affects quality of life by causing pain, limiting nutrition, compromising oral hygiene and intimacy, and complicating the ability to assess for cancer recurrence among other sequelae. When trismus presents acutely, further investigation for cancer recurrence, infection, fracture, or osteoradionecrosis should be initiated. Methods and Methods Chart review was performed to identify patients with acute worsening of trismus status following treatment for head and neck cancer with radiation or surgery. Results Two patients with acute trismus following prior treatment were identified and assessed. Early work-up of these two patients demonstrated acute infection in the first and cancer recurrence and fracture in the second. Conclusions Early identification of acute trismus enables prompt work-up and intervention for cancer recurrence, infection, fracture, or osteoradionecrosis, while preventing further complications and improving patient outcomes.